Lmx1a is essential for marginal cell differentiation and stria vascularis formation - Renauld, Justine M.; Iskusnykh, Igor Y.; Yamoah, Ebenezer N.; Smith, Richard J. H.; Affortit, Corentin; He, David Z.; Liu, Huizhan; Nichols, David; Bouma, Judith; Nayak, Mahesh K.; Weng, Xin; Qin, Tianli; et al. (Frontiers in Cell and Developmental Biology, 2025)
The transcription factor Lmx1a is widely expressed during early inner ear development, and mice lacking Lmx1a expression exhibit fusion of cochlear and vestibular hair cells and fail to form the ductus reuniens and the endolymphatic sac. Lmx1a dreher (Lmx1adr/dr), a recessive null mutation, results in non-functional Lmx1a expression, which expands from the outer sulcus to the stria vascularis and Reissner’s membrane. In the absence of Lmx1a, we observe a lack of proteins specific to the stria vascularis, such as BSND and KCNQ1 in marginal cells and CD44 in intermediate cells. Further analysis of the superficial epithelial cell layer at the expected stria vascularis location shows that the future intermediate cells migrate during embryonic development but subsequently disappear. Using antibodies against pendrin (Slc26a4) in Lmx1a knockout (KO) mice, we observe an expansion of pendrin expression across the stria vascularis and Reissner’s membrane. Moreover, in the absence of Lmx1a expression, no endocochlear potential is observed. These findings highlight the critical role of Lmx1a in inner ear development, particularly in the differentiation of cochlear and vestibular structures, the recruitment of pigment cells, and the expression of proteins essential for hearing and balance.